4-senses compact exhibit: novel tool to promote biodiversity - Mo’in, Nurfahana; Sapaat, Arney (2023)
Natural history exhibits serve as a valuable means of raising public awareness and disseminating information about biodiversity. It is one of the ways to attract all generations to mainstream biodiversity by exploring those components in more depth and detail. This research focuses on developing a 4-senses compact exhibit as an innovative tool to promote biodiversity, engaging the senses of sight, hearing, smell, and touch. The study involves students from primary and secondary schools, as the exhibit is intended for various locations such as education and research centers, shopping centers, and schools. The research employs pre- and post-treatment questionnaires to assess the effectiveness of the 4-sense compact exhibit in promoting biodiversity. The results suggest this exhibit is a potent and novel tool for enhancing biodiversity awareness among school students, fostering a deeper understanding and appreciation for nature. Its potential as an educational resource for both primary and secondary schools make it a promising tool to instill a sense of care and appreciation for biodiversity from a young age, contributing to a more environmentally conscious future